Evaluation of the Effects of STZ-Induced Diabetes on In Vitro Fertilization and Early Embryogenesis Processes - Hüseyin Aktuğ; Vildan Bozok Çetintaş; Ayşegül Uysal; Fatih Oltulu; Altuğ Yavaşoğlu; Saadet Özen Akarca; Buket Kosova (Journal of Diabetes Research)
The aim of this study was to investigate the effects of experimentally induced diabetes on (a) germ cells, (b) in vitro fertilization (IVF) success rate, and (c) gap junction and cell adhesion molecule gene and protein expressions during the early blastocyst period. Germ cells were obtained from healthy and diabetic rats, analyzed for number, motility, and morphology, and used for IVF. After reaching the early blastocyst stage, the expressions of genes encoding gap junction proteins and cell adhesion molecules were analyzed by quantitative RT-PCR. Histomorphologically and immunohistochemically analyses were also performed. Diabetes significantly affected sperm number and motility and the development of oocytes. Gene expressions of β-catenin and connexin family members and protein expressions of E-cadherin and connexin-43 significantly decreased in groups including germ cells isolated from diabetic rats. Connective tissue growth factor expression increased in groups that included sperm cells isolated from diabetic male rats, whereas mucin-1 expression increased in the group that included oocytes isolated from diabetic female rats paired with sperm cells isolated from healthy male rats. In summary, experimentally induced diabetes was found to influence gap junctions, cell adhesion molecules, and associated proteins which all have important roles in germ cell maturation, fertilization, and development.